Efficiency of natural ventilation in central greenhouse of Botanical garden in Kosice - Kovac, Martin; Kovacova, Katarina; Sedlakova, Anna (International Conference “Environmental Engineering”, 2017)
The object of paper is analysis of natural ventilation system in central greenhouse of Botanical garden in Kosice. The greenhouse was refurbished in 2015. The existing greenhouse covering from glass panels was replaced for polycarbonate panels. The ventilation system of central greenhouse is natural and there are used openings in covering (wall, roof). It is combination of thermally and wind driven ventilation. The main aim of contribution is to analyse different modes of natural ventilation during summer period mainly. The important factors that influence efficiency of natural ventilation in greenhouse are location and area of openings, temperature stratification in greenhouse, solar radiation level, wind speed and direction too. If the greenhouse is ventilated naturally only through external windows (roof windows are closed) the efficiency of ventilation is very poor. The defined modes of natural ventilation search the right location and size of opened windows in order to achieve the most efficiency ventilation of indoor environment. For this purpose the progressive dynamic simulation tool DesignBuilder is used where the geometrical and specific calculated model of whole central greenhouse was created.